Efficiency of osseodensification versus screw expansion technique for augmentation of narrow alveolar ridges: A comparative clinical study - Tofan , Nawfal H; Al-Hussaini , Ali HA; Mustafa , Nazih S (Journal of Baghdad College of Dentistry, 2024)
Background: Alveolar ridge expansion is proposed when the alveolar crest thickness is ≤5 mm. The screw expansion technique has been utilized for many years to expand narrow alveolar ridges. Recently, the osseodensification technique has been suggested as a reliable technique to expand narrow alveolar ridges with effective width gain and as little surgical operating time as possible. The current study aimed to compare osseodensification and screw expansion in terms of clinical width gain and operating time. Materials and methods: Forty implant osteotomies were performed in deficient horizontal alveolar ridges (3–5 mm). A total of 19 patients aged 21–59 years were randomized into two groups: the screw expansion group, which involved 20 osteotomies performed by screw expander drills, and osseodensification group, which comprised 20 osteotomies achieved by osseodensification drilling technique. One millimetre below the alveolar bone crest was measured with a bone caliper at two intervals (before implant osteotomy and after implant osteotomy), and operating time was assessed. Results: Before expansion, the mean alveolar ridge width was 4.20 ± 0.71 mm in the osseodensification group and 4.52 ± 0.53 mm in the screw-expansion group. No statistically significant difference in alveolar bone width before expansion was found between the groups (P > 0.05). After the expansion of the alveolar ridge with osseodensification or screw expansion techniques, the average ridge width was 5.48 ± 0.57 mm in the osseodensification group and 5.71 ± 0.53 mm in the screw-expansion group. Difference in width gain postoperatively between the groups was 0.09 mm, which was not statistically significant (P > 0.05). According to operating time, osseodensification consumed 6.21 ± 0.55 minutes, and screw expansion required 16.32 ± 0.60 minutes for a single implant with a significant difference between the groups (P < 0.0001). Conclusion: Alveolar bone expansion by osseodensification showed comparable width gain and less surgical operating time compared with expansion by screw expansion technique.